Existence theorem for nonconvex stochastic inclusions. (1994) - Kisielewicz, Michał
Abstract : An existence theorem for stochastic inclusions x t − x s ∈ ∫ s t F τ ( x τ ) d τ + ∫ s t G τ ( x τ ) d w τ + ∫ s t ∫ ℝ n H τ, z ( x r ) v ˜ ( d τ, d z ) with nonanticipative nonconvex-valued right-hand sides is proved.